Integration Research of Pantograph-Catenary Detection System for Intelligent Operation and Maintenance of Heavy-haul Locomotive - Jiejun LYU; Hongjun HE; Congjian JIANG (机车电传动)
Improving the on-line detection level of pantograph-catenary system and evaluating its service status has become a key problem to be solved in the construction of intelligent operation and maintenance of heavy-haul locomotive. Based on the introduction of the current situation of pantograph catenary system detection in service, the detection requirements, detection objects and technical challenges of pantograph catenary system were analyzed and summarized. Through the integrated research of pantograph catenary detection system and the comprehensive application of vehicle network, internet of things, cloud computing, image recognition and machine vision algorithm, an on-board pantograph catenary detection system suitable for heavy-duty locomotive with the functions of catenary state inspection, pantograph dynamic operation parameter detection and pantograph catenary dynamic interaction relationship detection was proposed. The test showed that the systems can realize on-line detection, fault diagnosis, intelligent prediction,emergency treatment and pantograph health management of pantograph-catenary system, improve the online detection and evaluation effect of pantograph-catenary system, and ensure the safety and reliability of line traction power supply.